ANALISIS VEGETASI LANTAI SEBAGAI PENAHAN LIMPASAN AIR DI SEKITAR MATA AIR - Fatimatuzzahra Fatimatuzzahra (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Water resources is essential for life. One of potential source is ground water springs. Floor vegetation act as rainwater retention,therefore rainfall does not become runoff instead infiltrate as ground water that is important.The purpose of this study was to analyze of floor vegetation (growth form shrubs, herbs, and grasses) around springs and study its role in the retention of water  infiltration. The study was conducted in June-October 2013 in Umbul Nila’s spring, Tulung, Klaten, Central Java and Mudal’s spring, Purwosari, Gunungkidul, D.I.Yogyakarta. The simple random sampling of 1m x1m quadrate method was used, for vegetation analyzes with a 15 samples of each springs. The results of analysis in Umbul Nila’s springs, was obtained 8 families, 17 species of vegetation floors and 5 families with 18 species around Mudal’s spring. The results of calculation, the highest INP value of 5 species vegetation in Umbul Nila: Heliotropium indicum 33,5%, Bidens pilosa 32%, Ischaemum triticeum 30,9%, Paspalum conjugatum 16,7%, dan Eleusine indica 11,6%.  whereas in Mudal: Ischaemum triticeum 28,6%, Elephantopus scaber 27,7%, Paspalum conjugatum 26%, Chromolaena odorata21,4%, Flemingia macrophylla16,9%. Diversity index (H ') in Umbul Nila (0,90) with low category and Mudal (1.02) includ of medium category. An index of similarity in both locations by 45,71%, meaning that a low floor vegetation similarity. The results of infiltration rate experiment using rain simulation, showed that the ability of water infiltration in Umbul Nila on herbs-covered land was 73% is higher than the land covered with grasses, shrubs, and base land. While in Mudal, shrub land covered by 97.17% compared to the land covered herbs, grasses, and base land. Keywords: Floor Vegetation, Springs, Infiltration, Umbul Nila, Mudal